Research Work in Secondary School аs an Object of Historical and Pedagogical Study - Valeriya Irza (Pedagogical Discourse, 2013)
The article analyzes existing psychological and pedagogical researches on the development issues of the research work in Ukrainian secondary school from the second half of the twentieth century. The article reveals the essence and studies the meaning of the «research work». Researches that deal with the content, forms and methods of experimental work are analyzed. The theoretical and practical features of using research work in the educational process in different ways are studied. Research work is treated as a method of personality development of the pupil, a factor of preparation for the professional self-determination, the method of stimulation of the cognitive activity of the pupil and the method for forming a culture of thinking of the pupils.